An 88-line MATLAB code for the parameterized level set method based topology optimization using radial basis functions - Wei, Peng; Li, Zuyu; Li, Xueping; Wang, Michael Yu (Structural and multidisciplinary optimization, 2018)
This paper presents a compact and efficient 88-line MATLAB code for the parameterized level set method based topology optimization using radial basis functions (RBFs), which is applied to minimize the compliance of a two-dimensional linear elastic structure. This parameterized level set method using radial basis functions can maintain a relatively smooth level set function with an approximate re-initialization scheme during the optimization process. It also has less dependency on initial designs due to its capability in nucleation of new holes inside the material domain. The MATLAB code and simple modifications are explained in detail with numerical examples. The 88-line code included in the appendix is intended for educational purposes.